The effect of construction demand on contract auctions: an experiment. Issue 3 (13th May 2014) - Soo, Alexander; Lan Oo, Bee
Abstract : Purpose: – The purpose of this paper is to present an experiment to test the effect of construction demand on the mark-up price level in construction contract auctions. Design/methodology/approach: – An experimental approach was adopted for this study. In a controlled laboratory environment, a first-price sealed bid auction was simulated with varying number of projects available over ten rounds to simulate changing construction demand. Two experimental treatments were run in parallel, one exhibiting a "booming" demand over time, and the other group with a "recession" scenario. The experiment involved student (inexperienced) bidders with a construction project management background. Findings: – The results show that inexperienced bidders do behave differently when subjected to varying levels of construction demand. Variations in the bid price level are affected by varying levels of construction demand and the general mark-up level for the bidders experiencing a booming scenario was higher on average compared to bidders subjected to the recession scenario. Research limitations/implications: – An identified limitation of this study is the use of student subjects in the experiment, thus the experiment results are limited in generalisation to inexperienced bidders. Further studies may be able to replicate the experiment with experienced industry practitioners to observe the results. Practical implications: – The results allow for industry practitioners to gain a stronger understanding of the effects of varying levels of construction demand and the need to consider construction demand in construction contracting. For construction clients, the level of construction demand may be used as an indicator to assist in the timing to call tenders to achieve a desirable price. For contractors, increased awareness of how demand affects competition and the price level will allow additional optimisations to be achieved in the bid price. Originality/value: – Construction demand has been widely known to be one of the key factors affecting contractors' bidding decisions. However, there has been little empirical investigation of the changes in bidders' behaviour due to varying levels of construction demand. This paper attempts to add to the empirical research knowledgebase through an experimental setting.